Remote English Teaching during Covid-19 Pandemic: Challenges and Lessons in Higher Education Teaching in Colombia (Research, Society and Development, 2022)
The objective of this article is to do bibliographic research lined up with the worldwide COVID-19 pandemic in which the main focus will be inclusion, Pygmalion effect as well as teaching and learning remotely. The basis is to gather different perspectives to build knowledge through exhaustive reading of books, doctoral dissertations, masters programs dissertations, current news, reliable sources of information, scientific papers, and own experience amongst others. The analysis of this bibliographic research will be useful for future research on topics related. Emotional and affective relations are important and have impact when facing English learning difficulties and when working to have inclusion. In the context of Covid-19, the learning and teaching conditions got complex when migrating to virtual classes. Remote teaching is not a solution to face learning and teaching difficulties. In this way, affection is the best tool for inclusive learning in virtual environments. It is said that one of the biggest barriers is teacher’s formation whose career is based on traditional pedagogy not easily adaptable to digital environments. This situation creates a deep feeling of frustration in teachers, which can be reflected in the low academic performance of English students. Several reflections will be made to encourage the actors involved in the teaching-learning process and in the educational system to ask themselves: Which are the challenges of remote teaching and learning during the Covid-19 pandemic being inclusive through the Pygmalion effect?